2021
DOI: 10.1037/lhb0000467
|View full text |Cite
|
Sign up to set email alerts
|

Technology for assessment and treatment of justice-involved youth: A systematic literature review.

Abstract: Objective: We conducted a systematic literature review of e-mental health technologies in juvenile justice contexts. Hypotheses: Our exploratory research questions were as follows: First, what types of e-mental health exist for justice-involved youth, their caregivers, and juvenile justice professionals? Second, what are the characteristics of studies that have examined these technologies? Third, what have studies found about the effectiveness, reliability, or validity of e-mental health in treating and assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…First, more research is needed not only on technologies that already have a growing evidence base in forensic and correctional mental health (e.g., videoconferencing, web platforms, and virtual reality) but also for technologies for which no or few studies exist (e.g., decision support systems, augmented reality, and wearable technology; Kip et al, 2018; Leach et al, 2022). Furthermore, empirically supported technologies designed specifically for justice-involved individuals are necessary (Grove et al, 2021). To increase access to such technologies for professionals, emphasis should be placed on transferring e-mental health solutions developed and validated via scientific research into commercially available products.…”
Section: Directions For Future Researchmentioning
confidence: 99%
See 2 more Smart Citations
“…First, more research is needed not only on technologies that already have a growing evidence base in forensic and correctional mental health (e.g., videoconferencing, web platforms, and virtual reality) but also for technologies for which no or few studies exist (e.g., decision support systems, augmented reality, and wearable technology; Kip et al, 2018; Leach et al, 2022). Furthermore, empirically supported technologies designed specifically for justice-involved individuals are necessary (Grove et al, 2021). To increase access to such technologies for professionals, emphasis should be placed on transferring e-mental health solutions developed and validated via scientific research into commercially available products.…”
Section: Directions For Future Researchmentioning
confidence: 99%
“…reviews having identified approximately 100 relevant articles grove et al, 2021;Kip et al, 2018;Leach et al, 2022). A catalyst for technology-based services in criminal justice settings has been the COVID-19 pandemic which necessitated a rapid increase in the adoption rate to comply with physical distancing regulations (Bernhard et al, 2021;Kois et al, 2021).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Digital health interventions that combine motivation-enhancement and accurate peer norms may be especially well-suited to treat CINI youth in justice settings because they are accessible, customizable, portable, and show evidence of reducing cannabis use [ 34 - 39 ]. Among adolescents who receive brief computerized SU treatments [ 40 ], effects appear to fade over time [ 41 ], suggesting that adjunct treatments may be needed to help sustain gains.…”
Section: Introductionmentioning
confidence: 99%
“…The second article, by Grove et al (2021), presents the results of a systematic review of e-mental health for justice-involved youth to explore which assessment and treatment technologies have been developed or investigated, the characteristics of the available research, the extent of efficacy evidence, and the advantages and disadvantages. Given the increasing use of technology to deliver or supplement behavioral health assessment and treatment, including among justice-involved individuals, tough systematic reviews such as this one simultaneously offer a "state of the field" summary and a nuanced perspective on this important topic.…”
mentioning
confidence: 99%